Standardized Innovative Polygon Trend Analysis for Climate Change Assessment (S-IPTA) - Alashan, Sadik; Abu Arra, Ahmad; Sisman, Eyup (SPRINGER BASEL AG, 2024)
Research and applications on trend analysis have recently been on the agenda and are top priorities in many disciplines due to the effects of climate change. After a thorough evaluation of the literature, it is noted that different hydro-meteorological variables, such as precipitation, temperature, etc., are studied and analyzed individually. This research proposes a new innovative polygon trend analysis application (S-IPTA) using the standardization concept to fill this gap in classical trend applications and comprehensively compare the trends of different variables to temporal and spatial patterns. Firstly, using statistical standardization, S-IPTA adjusts the original data sets and makes them dimensionless. Then, the innovative trend analyses are conducted and interpreted on one single graph (S-IPTA). The S-IPTA methodology is applied to monthly precipitation and temperature time series of Konya Basin in T & uuml;rkiye at ten meteorological stations between 1959 and 2022. For precipitation, the S-IPTA did not exhibit a consistent polygon across all stations within the study area, while the temperature polygon was more regular, indicating that the temperature mean was generally stable with a positive trend. Also, S-IPTA shows the difference between the average value for each month and the newly proposed long-term average value (0). S-IPTA also provides a basis for a better interpretation of climate change and its effects by providing a common denominator for various trend characteristics, such as trend magnitudes and trend transitions in different hydro-meteorological time series.
Keywords: Time series; trend; precipitation; temperature; Innovative Trend Analysis (ITA); Innovative Polygon Trend Analysis (IPTA); KONYA CLOSED BASIN; EXTREME PRECIPITATION; DROUGHT; INDEXES; Geochemistry & Geophysics